Роль методологічних правил у проведенні порівняльно-правових досліджень - Баранова, Юлія Олегівна; Баранова, Юлия Олеговна; Baranova, Julija (Одеса : Юрид. л-ра, 2012)
In the article author determination of methodological rules is presented governed, existing in literature developments are investigational through this question. On the basis of system analysis classification of methodological rules is offered, and also their value is identified.
Баранова Ю. О. Роль методологічних правил у проведенні порівняльно-правових досліджень / Ю.О. Баранова // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 186-193.
Keywords: порівняльно-правові дослідження; методологія порівняльно-правового пізнання; методологічні правила; сравнительно-правовые исследования; методология сравнительно-правового познания; методологические правила; comparative-legal researches; methodology of comparative law cognition; methodological rules